The insert effect of cellulose nanofiber layer on glass fiber‐reinforced plastic laminates and their flexural properties. Issue 3 (16th April 2019) - Kurita, Hiroki; Xie, Yingmei; Katabira, Kenichi; Honda, Risa; Narita, Fumio
Abstract: Cellulose nanofibers (CNFs) have the potential to adhere glass fiber‐reinforced plastics (GFRPs) without a decrease in their mechanical properties. In this study, we inserted two CNF layers between GFRP laminates and evaluated their flexural properties. The insert of epoxy resin with CNF of 0.1 wt% layers, increased the flexural strength of GFRP by 125%, whereas the flexural modulus of CNF layer inserted GFRP laminates was constant (28 ± 0.67 GPa). Moreover, we evaluated the flexural properties of a single CNF layer and revealed that even an extremely slight CNF (0.04 wt%) addition drastically increased the flexural strength and fracture elongation of epoxy resin by 130% and 180%, respectively.